Strategi Pengembangan Pantai Walakiri Sebagai Destinasi Wisata Di Kabupaten Sumba Timur - Perdana, Ryan Adiyat (Tourism, Hospitality And Culture Insights Journal, 2024)
Indonesia continues to strive to develop the tourism industry to achieve a balanced foreign trade balance and improve the local economy. Sumba Island, especially East Sumba Regency, has tremendous natural and cultural tourism potential, one of which is Walakiri Beach. This beach is famous for the unique beauty of mangrove trees, especially at sunset. This research aims to formulate a development strategy for Walakiri Beach as a leading tourist destination in Watumbaka Village, Pandawai District, East Sumba Regency, East Nusa Tenggara. The method used was descriptive qualitative with SWOT analysis. The results showed that Walakiri Beach has significant strengths and opportunities to be developed, although there are some weaknesses and threats that need to be addressed. Development strategies include increasing public awareness to protect the environment, structuring facilities, and effective tourism promotion. The implementation of these strategies is expected to increase tourist attraction, local community welfare, and regional income.